International trade in indigenous cultural heritage : legal and policy issues - Graber, Christoph B.; Kuprecht, Karolina; Lai, Jessica C. , 1985- (Edward Elgar, 2012)
This topical book brings to the fore new and standard-setting research into the connection between indigenous cultural heritage, international trade and economic development of indigenous peoples